PENGARUH POLA REKRUITMEN PEGAWAI NEGERI SIPIL TERHADAP EFEKTIFITAS ORGANISAI (SUATU STUDI PADA BADAN KEPEGAWAIAN DAERAH PROVINSI MALUKU UTARA) - HANGEWA, FALENTINA (Sam Ratulangi University, 2013)
Abstract : Research in the framework of the preparation of the thesis degree * ( S - 1 ) to move from the initial observation that the effectiveness of the organization indicated BKD North Maluku province remains low . This is presumably related to the recruitment pattern of the less professional . Thus , this study aims to analyze how the influence recruitment patterns of the effectiveness of the organization BKD North Maluku province .This study uses a quantitative approach to the application of descriptive and explanatory survey . Data were collected through questionnaires distributed to instrument 60 respondents BKD employees . Once the data is collected , then analyzed by applying analysis techniques by applying frequency table analysis techniques , product moment correlation and simple regression . The results showed that recruitment is one of the very menentukkan determinant factor of success or effectiveness of the organization . Rekruitmn pattern which ignores aspects of employee competence and contaminated with corruption behavior will reflect badly on the achievement of organizational effectiveness . Not optimal achievement of organizational effectiveness BKD North Maluku province is related to employee recruitment patterns are less professional .The conclusion that can be drawn from these results is that the arrangement of the pattern of recruitment of employees with respect to the organization's needs for quality human resources will be able to push the organization's ability Regional Employment Board of North Maluku Province bias ahead to adapt to the environment , to increase the productivity of the organization and also be able to increase job satisfaction .Keywords : Recruitment , Competence , Professionalism , organization effectiveness .